Valorization of glycerol via esterification of oleic acid and glycerol under microwave heating using zinc oxide as a catalyst - Thiamsinsangwon, Puttiporn; Yuwansri, La-ongthip; Kositanont, Chayanoot; Mens, Weerinda (Frontiers in Engineering Innovation Research, 2026)
This study investigated the esterification of oleic acid with glycerol for value-added glycerides production of using zinc oxide as the catalyst, with emphasis on evaluating the effects of heating mode, reactant molar ratio, and reaction temperature on oleic acid conversion and monoglyceride yield (MG yield) were evaluated. The results showed that microwave heating clearly enhanced MG yield compared with a conventional mechanically stirred reactor. The suitable condition for monoglyceride production was an oleic acid-to-glycerol molar ratio of 1:4, a ZnO catalyst loading of 0.5 wt.% based on oleic acid, a reaction temperature of 160 °C, and a reaction time of 30 min. Under this condition, oleic acid conversion, MG selectivity and MG yield were 63.1%, 75.4%, and 47.6%, respectively. In contrast, the conventional mechanically stirred reactor provided an MG yield of only 28.1% under the same condition. In addition, the oleic acid-to-glycerol molar ratio of 1:4 gave a higher MG yield than the other investigated molar ratios, indicating that an appropriate excess of glycerol promoted the formation of the target product. Although increasing the reaction temperature to 180 and 200 °C enhanced oleic acid conversion, the MG yield decreased to 40.5% and 38.9%, respectively, possibly due to the acceleration of consecutive reactions from MG to diglyceride (DG) and triglyceride (TG). Therefore, microwave-assisted esterification at a molar ratio of 1:4, 160 °C, and 30 min was identified as a suitable condition for monoglyceride production from glycerol under the investigated conditions.